Genetic recombination between mouse type C RNA viruses: a mechanism for endogenous viral gene amplification in mammalian cells. - Barbacid, M (1978)
A strategy based on the identification of type-specific antigenic determinants in the transitional products of gag (p15, p12, and p30 proteins), pol (reverse transcriptase), and env (gp70 glycoproteins) genes of mammalian type C viruses has been used to study genetic recombination between these RNA viruses. By this approach, recombinants involving exogenous and endogenous mouse type C viruses have been identified and genetically mapped. Analogous techniques have been applied to investigate the genetic relationships between different classes of endogenous virus that exist within the same mouse cells. Proteins of the inducible class of xenotropic virus were shown to exhibit extensive antigenic homology with the gag but not the env gene products of the ecotropic virus class. Instead, the env gene-coded glycoproteins of the inducible and noninducible xenotropic virus classes possessed striking antigenic relatedness. These results, as well as supporting findings from molecular hybridization, favor the concept that the inducible xenotropic virus of mouse cells arose by a recombinational mechanism involving the progenitors of the other two endogenous virus classes.